Trainee Surgeons Affect Operative Time but not Outcome in Minimally Invasive Total Hip Arthroplasty - Markus Weber (Nature Portfolio, 2017)
Abstract Training of young surgeons in total hip arthroplasty (THA) is crucial, but might affect operative time and outcome especially in minimally invasive (MIS) THA. We asked whether the learning curve of orthopaedic residents trained on MIS THA has an impact on (1) operative time (2) complication rates and (3) early postoperative outcome. In a retrospective analysis of over 1000 MIS THAs from our institutional joint registry, operative time, complication rates, patient reported outcome measures (Western Ontario and McMaster Universities Arthritis Index [WOMAC] and Euro-Qol 5D-5L [EQ-5D]) within the first year and responder rates for positive outcome as defined by the Outcome Measures in Rheumatology and Osteoarthritis Research Society International consensus responder (OMERACT-OARSI) criteria were compared between trainee and senior surgeons. Mean operative time was nine minutes longer for trainees compared to senior surgeons (78.1 ± 25.4 min versus 69.3 ± 23.8 min, p < 0.001). Dislocation (p = 0.21), intraoperative fracture (p = 0.84) and infection rates (p = 0.58) were comparably low in both groups. Both trainee and senior THAs showed excellent improvement of EQ-5D (0.34 ± 0.26 versus 0.32 ± 0.23, p = 0.40) and WOMAC (45.9 ± 22.1 versus 44.9 ± 20.0, p = 0.51) within the first year after surgery without clinical relevant differences. Similarly, responder rates for positive outcome were comparable between trainees with 92.9% and senior surgeons with 95.2% (p = 0.17). MIS THA seems to be a safe procedure during the learning curve of young orthopaedic specialists, but requires higher operative time.